The design and development of semi-automated paste filling machine for spicy shrimp paste - Sharif Z.M.; Rahim M.Z.; Ibrahim M.R.; Othman M.S. (Mattingley Publishing, 2023)
Filling; Quality control; Auxiliary systems; Design and Development; Filling process; Food industries; Paste fillings; Speed sensors; Spicy shrimp paste; Volume sensors; Automation